CO2-plume geothermal: Power net generation from 3D fluvial aquifers. (15th February 2023) - Norouzi, Amir Mohammad; Pouranian, Fatemeh; Rabbani, Arash; Fowler, Neil; Gluyas, Jon; Niasar, Vahid; Ezekiel, Justin; Babaei, Masoud
Abstract: Previously CO2, as a heat-extraction fluid, has been proposed as a superior substitute for brine in geothermal energy extraction. Hence, the new concept of CO2 -plume geothermal (CPG) is suggested to generate heat from geothermal aquifers using CO2 as the working fluid. In January 2015, a CPG-thermosiphon system commenced at the SECARB Cranfield Site, Mississippi. By utilizing CO2, the demand for the pumping power is greatly reduced due to the thermosiphon effect at the production well. However, there are still parameters such as aquifer thermal depletion, required high injection rates, and CO2 -plume establishment time, that hinder CPG from becoming viable. Moreover, the fluvial nature of sedimentary aquifers significantly affects the heat and mass transfer inside the aquifer, as well as the system performance. In the present study, a direct-CO2 thermosiphon system is considered that produces electricity from a 3D braided-fluvial sedimentary aquifer by providing an excess pressure at the surface that is used in the turbine. The system performance and net power output are analysed in 15 3D fluvial heterogeneous – with channels' widths of 50, 100, and 150 m – and three homogeneous aquifer realizations with different CO2 injection rates. It is observed that the presence of fluvial channels significantly increases the aquifer thermal depletion pace (22%–120%) and therefore, reduces the system's performance up to about 75%. Additionally, it is found that the CPG system with the CO2 injection rate of 50 kg/s and the I-P line parallel to the channels provides the maximum cycle operation time (44 years), as well as the optimum performance for the heterogeneous cases of the present study by providing about 0.06–0.12 TWh energy during the simulation time of 50 years. Also, to prevent rapid drops in excess pressure, a system with a yearly adjustable injection rate is implemented, which prevents the production well bottomhole temperature to fall below 80 °C. Highlights: Power analysis of a direct-CO2 thermosiphon system from a 3D braided fluvial aquifer. Fluvial heterogeneity reduces the system net power up to 75%. CO2 injection rate of 50 kg/s has the optimum performance for heterogeneous aquifers. A CO2 flowrate of 50 kg/s provides Pnet, avg of 0.3 MWe over 44 years for a homogeneous aquifer. The cumulative electricity output of CPG over 50 years is in order of tenth of TWh.